SOSIALISASI PENANGANAN DAN PENCEGAHAN CEDERA DALAM OLAHRAGA - Sayyid Muhammad Murtadho; Wildan Hidayat; Dindin Abidin; Azi Faiz Ridlo (An-Nizam, 2023)
Sport is an activity to train one's body, both physically and spiritually. The purpose of exercising is to be healthy and also provide a fitness effect for the body. Exercise not only helps in training the muscles but also helps the circulation of blood and oxygen in the body to be smooth, that is why exercising can have an overall fitness effect on the human body. Sport can be said as one of the physical activities that is very beneficial for one's body, mind, and soul. The method used in this activity is socializing to the community to create safe sports habits (safety). Based on the results of observations in Setialaksana village, there are still many people who do not care about safe sports. Because if we exercise and don't use the rules correctly it can cause injury. For example, when people start exercising before they don't warm up (streching), this can result in injury to the muscles of the body. because it needs outreach for the community to create a safe sport. The individual program in this activity was carried out on February 28 2023 at the Setialaksana Village Office, Cabangbungin District. The intended targets in socialization to create safe sports habits for the community are teenagers and the local community. present in this individual work program and the activities run smoothly. With this socialization, it is hoped can add insight regarding preventing injuries during sports safely for the community.